Analysis & Simulation Modeling for Brake Control System of Civil Aircraft - Chen, Guohui; Liu, Jinsong; Qianggang; Ma, Xiaojun; Zhangjiao; Luo, Kexun (IET Conference Proceedings, 2018)
Brake control system includes control law, hydraulic valves and sensors, normally the simulation model is not so accurate if only use Simulink model simulation result. This document integrating Simscape model and Simulink model, the physical model based on hydraulic valves and sensors structure could be created by Simscape, while behavior model based on requirements could be created by Simulink, this is an integration of physical and behavior model which is accurate enough for the development, validation and verification of brake control system.